The oxygen reduction reaction on Pt(111) and Pt(100) surfaces substituted by subsurface Cu: a theoretical perspective1. Issue 21 (7th June 2015) - Li, Kai; Li, Yang; Wang, Ying; He, Feng; Jiao, Menggai; Tang, Hao; Wu, Zhijian
<x xml:space="preserve">Abstract</x> The ORR reaction activity is improved on Pt/Cu(111) and hindered on Pt/Cu(100), compared with pure Pt(111) and Pt(100).